The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3138/jcfs.46.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disclosure Between Marital Couples: A Comparative Study Between Singapore and Greek Couples

Abstract: This study explored the effects of spousal and self-disclosure on perceived marital satisfaction among Greek and Singaporean couples. The sample included 77 Singaporean couples and 116 Greek couples. APIM and multi-group modeling techniques were applied simultaneously. Results indicated that wife’s and husband’s self-disclosure were similarly able to predict their own marital satisfaction for both countries. Partner effects were different within and between the groups. With Singaporean couples, wife’s self-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Reviewed articles have used quantitative methods, such as surveys and questionnaires (e.g., Gubbins et al 2010;Quek et al, 2015). Whereas qualitative methods have also been used for data collection to gain insights on how people respond and express themselves in relationships.…”
Section: Prevalent Research Methodologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Reviewed articles have used quantitative methods, such as surveys and questionnaires (e.g., Gubbins et al 2010;Quek et al, 2015). Whereas qualitative methods have also been used for data collection to gain insights on how people respond and express themselves in relationships.…”
Section: Prevalent Research Methodologiesmentioning
confidence: 99%
“…4), show up in relationships, take initiatives, freely share thoughts, emotions, and feelings without worrying about the consequences with an intention to connect and hope for it to be received. Many studies have used the term "selfdisclosure" to explain this phenomenon of vulnerability in bits and pieces (e.g., Welker et al, 2014;Quek et al, 2015). Much research has concluded self-disclosure as a powerful communication tool to nourish and enhance emotional intimacy and satisfaction in any relationship (Collin & miller, 1994;Prager et al, 2013).…”
Section: Vulnerability and Its Impactmentioning
confidence: 99%
See 3 more Smart Citations